Brazilian law of inclusion: an applied analysis of the correlation of bioethical principles - Rocha, Rosylane Nascimento das Mercês; Cruz Bezerra, Josierton; Cortes Fernandes, Francisco; Correia, Mónica; Nunes, Rui (Acta Bioethica, 2022)
Objective: The present study aims to analyse whether bioethical principles are present in the Brazilian Law of Inclusion of the Disabled Person. Methods: The study is based on a textual analysis of Law No. 13.146, of July 6, 2015 (Brazilian Law of Inclusion) using a content analysis technique regarding the bioethical principles of beneficence, nonmaleficence, justice and autonomy. A qualitative analysis was conducted based on the concepts of these bioethical principles and their expression in the articles laid down in the Statute of the Disabled Person. Results: The obtained results demonstrate that the primary articles of the Brazilian Law of Inclusion correlate with the aforementioned bioethical principles according to the conceptualisation of each principle. Conclusion: The articles of the Brazilian Law of Inclusion, published on July 6, 2015, under the provisions of the Federal Constitution of 1988 and the Convention on the Rights of Persons with Disabilities, demonstrate a correlation with the stated bioethical principles.